2012
DOI: 10.1097/lgt.0b013e3182320f0c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conventional Cervical Cytology Versus Visual Inspection With Acetic Acid Among Human Immunodeficiency Virus–Infected Women in Western Kenya

Abstract: Objective To determine the accuracy of visual inspection with Acetic Acid (VIA) versus conventional Pap smear as a screening tool for cervical intraepithelial neoplasia (CIN)/cancer among HIV-infected women. Materials and Methods 150 HIV-infected women attending the Moi Teaching and Referral Hospital HIV clinic in Eldoret underwent conventional Pap smear, VIA, colposcopy and biopsy. VIA and Pap smears were done by nurses while colposcopy and biopsy were done by a physician. Receiver Operating Characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 18 publications
(14 reference statements)
3
48
1
Order By: Relevance
“…810 The specificity point estimate of DC for CIN2+ that we report (58%) lies near the lower end of the range (51% – 83%) reported for unaided VIA in these studies. 810 The specificity point estimate of cytology for CIN2+ that we report (58%) is slightly lower but comparable to that of Mabeya et al (66%), 9 while both are substantially lower than that reported by Sahasrabuddhe et al (83%). 8 Our lower specificity of cytology could be because our histopathology gold standard was based solely on punch biopsy specimens.…”
Section: Discussionsupporting
confidence: 71%
“…810 The specificity point estimate of DC for CIN2+ that we report (58%) lies near the lower end of the range (51% – 83%) reported for unaided VIA in these studies. 810 The specificity point estimate of cytology for CIN2+ that we report (58%) is slightly lower but comparable to that of Mabeya et al (66%), 9 while both are substantially lower than that reported by Sahasrabuddhe et al (83%). 8 Our lower specificity of cytology could be because our histopathology gold standard was based solely on punch biopsy specimens.…”
Section: Discussionsupporting
confidence: 71%
“…The prevalence of 28.2% as found in this study is high but comparable to 27% reported in UK by Hotonu et al (2010) and 31.3% in Maiduguri, Northern Nigeria by Chama et al (2005). It is however lower than 68.3 and 43.7% prevalence rates reported in Jos, Nigeria by Agaba et al (2009) and in Kenya by Mabeya et al (2012). A lower rate of 12.6% was reported in Enugu by Dim et al (2011).…”
Section: Discussioncontrasting
confidence: 46%
“…Multiple screening methods have demonstrated accuracy in LMICs, 91,100 with the ability to incorporate mobile technologies 101,102 and well-trained non-physician clinicians to extend services. 96,102,103 Likewise, when precancerous lesions are identified, multiple treatment options demonstrate excellent efficacy in LMICs.…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%